2020
DOI: 10.3390/ijerph17176113
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Prospective Memory: A Retrospective Study in Different Clinical Populations

Abstract: Prospective memory (PM) is essential in everyday life because it concerns the ability to remember to perform an intended action in the future. This ability could be influenced by poor sleep quality, the role of which, however, is still being debated. To examine the role of sleep quality in PM in depth, we decided to perform a retrospective naturalistic study examining different clinical populations with a primary sleep disorder or comorbid low sleep quality. If sleep is important for PM function, we could expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Our prospective memory paradigm can be considered as a routine everyday task which may be more relevant to clinical populations for which healthcare actions needs to be made regularly, e.g., in patients on cART, in whom deficits in neurocognitive functions are frequently reported [ 60 ]. Sleeping after encoding appears to influence and strengthen the memory to perform an intended action at a planned time, suggesting a beneficial effect of sleep on prospective memory [ 61 , 62 ], although this point is still being debated [ 40 , 63 ]. Reduced sleep quality and quantity are connected to altered and diminished encoding and memory consolidation abilities over time [ 23 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our prospective memory paradigm can be considered as a routine everyday task which may be more relevant to clinical populations for which healthcare actions needs to be made regularly, e.g., in patients on cART, in whom deficits in neurocognitive functions are frequently reported [ 60 ]. Sleeping after encoding appears to influence and strengthen the memory to perform an intended action at a planned time, suggesting a beneficial effect of sleep on prospective memory [ 61 , 62 ], although this point is still being debated [ 40 , 63 ]. Reduced sleep quality and quantity are connected to altered and diminished encoding and memory consolidation abilities over time [ 23 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that better scores for several sleep parameters (sleep efficiency and latency) were positively associated with this prospective memory task in healthy controls but not in PLWH suggests that sleep quality is not the main factor of memory performance [ 40 , 63 ]. Indeed, the deteriorated fragmentation index in PLWH was not correlated with any performance index of the task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research studies have shown significant impairments in vigilance, memory and psychomotor control [30][31][32] but, on the contrary, other works have found no clear results of cognitive performance impairments in insomniac patients [33][34][35]. With some surprise, a positive relationship between insomnia and cognitive performance has been recently highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the relationship between memory and time perception, in recent years, it has been widely shown as a sleep effect on both types of memory, although the relationship between sleep and prospective memory is still under debate. Interestingly, a recent study [ 75 ] speculated that the lower accuracy in executing prospective memory at bedtime could be related to the higher pressure of the homeostatic sleep regulation process [ 76 ] and decreased alertness levels. Thus, it is possible to expect that people with altered sleep timing and regulation, as well as lower dispositional mindfulness, should be impaired in memory functioning during the home confinement.…”
Section: Introductionmentioning
confidence: 99%